Analysis of extractable basic nitrogen compounds in Buliangou subbituminous coal by positive-ion ESI FT-ICR MS. (1st November 2015) - Kong, Jiao; Wei, Xian-Yong; Yan, Hong-Lei; Li, Zhan-Ku; Zhao, Mei-Xia; Li, Yan; Zong, Zhi-Min
Highlights: Numerous basic species in extracts from Buliangou subbituminous coal were detected. N1 O x class species with DBE = 4–25 and CN = 12–38 are dominant in the extracts. Basic nitrogen species extracted with methanol have lower DBE values and CNs. Basic nitrogen species in the extracts are mainly condensed N -heterocyclic aromatics. Abstract: Buliangou subbituminous coal (BSBC) was sequentially extracted with carbon disulfide, methanol, and acetone under ultrasonic irradiation to afford extracts 1–3 (E1 –E3 ). All the extracts were analyzed with a positive-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS). In total, 11.11% of organic matter in BSBC was extracted with the three solvents. According to analysis with positive-ion ESI FT-ICR MS, the molecular masses of basic nitrogen compounds (BNCs) in E1 –E3 range from 200 to 600  u and dominate from 250 to 450  u . The BNCs detected are mainly N1 O x ( x  = 0–2) and N2 O y ( y  = 0 and 1) with 4–25 of double bond equivalent (DBE) values and 12–38 of carbon numbers (CNs). The BNCs in E2 have lower DBE values (4–16) and CNs (14–28). According to DBE distributions, molecular core structures of most N1 O x classes should be aromatic rings, including benzene, pyridine, quinoline, and acridine rings. Moreover, core structures of most N1 O x moieties connected with an amino group or condensed with a pyrrole ring are characteristic structures for N2 O y classes in E1 –E3 . In addition, a small amount of amines (DBE < 4) were also identified in the extracts. Positive-ion ESI FT-ICR MS proved to be a powerful tool for identifying extractable BNCs in coals.